Optimalisasi Pema Mahasiswa Bersama Dosen dalam Rangka Meningkatkan Tri Dharma Perguruan Tinggi - Marpaung, Jamiludin; Tiara Putri Sayani; M Akmal Suhardi; Ramzy Ikram; Nazmma Ainina Berutu; Annisa Fadilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to determine the optimization of implementation carried out by students and lecturers in order to improve the Tri Dharma of Higher Education. The type of research used in this research is a qualitative method with a sociological approach. The results of this research are that collaboration between students and lecturers plays an important role in improving Tri Dharma in Hulu Village. Students are involved in community service activities that provide concrete solutions to local problems. Lecturers play an important role in directing relevant research and guiding students in community service projects.